2020
DOI: 10.2147/ndt.s240377
|View full text |Cite
|
Sign up to set email alerts
|

<p>Drug Attitude, Insight, and Patient’s Knowledge About Prescribed Antipsychotics in Schizophrenia: A Cross-Sectional Survey</p>

Abstract: Introduction: While patients' perspectives toward pharmacotherapy are expected to be directly influenced by their motivation and understanding of the treatment that they are currently receiving, no study has comprehensively investigated the impact of insight into illness and knowledge for the ongoing pharmacotherapy on the attitude towards drug treatment among patients with schizophrenia. Materials and Methods: One hundred forty-eight Japanese outpatients diagnosed with schizophrenia, according to the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In this respect, the intensive and recovery centered treatment ideally provided by specialized early intervention programs facilitates the development of a therapeutic relationship [63]. Apart from strategies aimed at improving adherence to medication such as the use of long-acting injectable (LAI) antipsychotics [64,65], motivational interviews, web-based psychoeducation, or SMS medication reminders [66], targeting insight seems to be useful to enhance adherence through a synergic process, which in turn improves outcome [67], particularly in terms of functional recovery. Furthermore, our finding that gain in adherence appears to occur earlier than improvement in insight throughout the program is interesting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the intensive and recovery centered treatment ideally provided by specialized early intervention programs facilitates the development of a therapeutic relationship [63]. Apart from strategies aimed at improving adherence to medication such as the use of long-acting injectable (LAI) antipsychotics [64,65], motivational interviews, web-based psychoeducation, or SMS medication reminders [66], targeting insight seems to be useful to enhance adherence through a synergic process, which in turn improves outcome [67], particularly in terms of functional recovery. Furthermore, our finding that gain in adherence appears to occur earlier than improvement in insight throughout the program is interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, patients’ attitudes toward medication were not considered. In this respect, one cross-sectional study looked at the impact of insight into illness and the global knowledge of patients with schizophrenia about their ongoing medication on their attitudes toward drug treatment [ 67 ]. The results concluded that good insight is associated with more favorable attitudes toward antipsychotic medication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the attitude toward and willingness to use LAIs of community-based patients with schizophrenia will also be affected by the characteristics of family monitoring and the coexistence of disease outcome ( 30 , 31 ). Our study showed that patients' age, marital status, care ability, outpatient adherence, antipsychotic adherence, and attitude toward oral antipsychotics were important predictor of patients' attitudes toward LAI antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Social and environmental factors such as relationship with clinicians, living situation and stigma of the illness, influence adherence at both consumer and service levels. There is a growing number of review papers on adherence; however, these reviews have given little attention to the impact of attitudes towards medication and adherence in people experiencing schizophrenia (Nagai et al, 2020). This population experiences higher medication non-adherence incidence rates (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the development of effective interventions to improve adherence, and in turn reduce the distress caused by the experiences of schizophrenia is urgently needed (Nagai et al, 2020). Addressing the impact of attitude on medication adherence in this population is overdue.…”
Section: Introductionmentioning
confidence: 99%